The Polish Catholic Church and the Public Memory of the Shoah: Between Mnemonic Backlash and Settling Accounts with the Past - Nowicka-Franczak, Magdalena (Acta Poloniae Historica, 2024)
The paper discusses the Polish Catholic Church’s ambiguous contribution to the public debate on settling accounts with the Polish-Jewish wartime past. The Church is an actor of right-wing historical politics, which casts Poles in the role of the primary victims of the war but is reluctant to speak out on the Shoah. The growing scholarly interest in the dark chapters in the history of Catholic-Jewish relations, which brings to light the Church’s institutional and symbolic responsibility for its attitude towards the persecuted Jewish community, has not translated directly into greater visibility of the issue in the mainstream media. However, the Church’s ceremonial indifference towards the memory of the Shoah is not resistant to changes in the historiography of the Shoah. The Church’s stance in the debate on the memory of the Shoah insufficiently recognises its position about the Jewish tragedy. On the other hand, it includes the actions undertaken by Father Wojciech Lemański and Bishop Rafał Markowski to commemorate the Jewish victims. The recognition of this cleavage aligns with sociological analyses of axiological divisions in Polish society.